A COMPARISON BETWEEN PRESENATATION TIME AND DELAY IN SURGERY IN SIMPLE AND ADVANCED APPENDICITIS - Fahim, Fraz; Shirjeel, Sharoon (Journal of Ayub Medical College Abbottabad, 2005)
Background: Acute appendicitis is the most common cause of acute abdomen. Serial examinations and investigations increase diagnostic accuracy. But this causes delay, which may result in gangrene and perforation. Our aim is to determine the affect of delay by the patient as well as by the physician on the stage of the disease as determined intraoperatively and to determine the percentage of negative appendectomies. Methods: 102 consecutive patients presenting to the Mayo Hospital emergency, undergoing appendectomy between February and April, 2002 comprise the study group. Data was tabulated and analyzed. The delay by the patient in presenting to emergency was called the patient’s delay and the in-hospital delay before the actual operation called the physician’s delay were calculated. The appendicitis was divided into two groups i.e. simple appendicitis which included acutely inflamed appendices and grossly mildly or non inflamed but histopathologically inflamed appendicitis and advanced appendicitis which included gangrenous and perforated cases. Results: The percentage of negative appendectomy in our center was 5.9%. Patients’ delay averaged 2.59 days and 2.43 days in simple and advanced appendicitis. A prolonged average delay period of 6.12 day was seen in misdiagnosed cases. The mean delay was not significantly different. 86.3% of the patients were operated within 12 hours of presentation. The mean physician’s delay was 9.24 hours. It was significantly shorter for advanced appendicitis as compared to simple appendicitis. Conclusions: Patient’s delay was not associated with advanced appendicitis. It is recognizable clinically and gets operated two hours earlier on average. There is a significant lag period of observation leading to a physician delay in simple appendicitis, contributing possibly to, increased morbidity. However there is an increased need to use ultrasonography and CT in the emergency setting to diagnose appendicitis in case of doubt. Key Words: Appendicitis, negative appendectomies, appendix.